Calvyn en die Calvinisme - Engelbrecht, B. J. (Hervormde teologiese studies, 1988)
Calvin and Calvinism The theology of Calvin had and still has a worldwide influence. During the course of history, theologians suggested various themes as the central theme of Calvin's theology around which it is possible to structure all the aspects of his theological thought to a coherent system. It is a question if this is really possible writhout a lesser or greater measure of distortion of Calvin's own theological thought. In this article two 'central themes' are treated, that is the theme of the soli Deo gloria and the theme of the sola et tola Scriptura. In each case Calvin's own thinking on the subject concerned, is described and then the various interpretations in history of the theme concerned are treated. In this way trends in calvinistic thinking and groups such as Kuypers Neo-Calvinism, the Social Gospel, the rationalistic Orthodoxism, the methodistic Pietism, the Enlightenment, theological Liberalism and modem hermeneutics are broached. Finally, ensuing from this, the most important issues to be adrcssed presently in Calvinistic thought, are identified.